(untitled) (Damascus University Journal of educational and Psychologyical sciences, 2021)
The aim of this research was to know the availability of the learning organization dimensions in the schools of the first cycle of basic education in Damascus from the point of view of the members of the research sample, as well as the differences in the answers’ grades of the sample members according to the research variables (gender, qualification and years of experience). The research used the analytical descriptive method, and a questionnaire consisting of (52) items was used and was distributed to a sample of (200) teachers working in the schools of the first cycle of basic education in Damascus city. The results showed that the degree of the availability of the learning organization dimensions in the schools of the first cycle of basic education in Damascus city from the point of view of the research sample was medium. In addition, the research also showed that there were no significant differences between the averages of the individuals’ responses of the research sample due to the gender variable. In contrast, there were statistically significant differences due to the scientific qualification variable in favor of the holders of both the intermediate institute certificate and the university degree. Moreover, there were statistically significant differences due to the years of experience for those of less than five years.